2020
DOI: 10.1136/bcr-2019-233135
|View full text |Cite
|
Sign up to set email alerts
|

Faecal microbiota transplantation (FMT) with dietary therapy for acute severe ulcerative colitis

Abstract: A 19-year-old man presented with acute severe ulcerative colitis. He was taking azathioprine (therapeutic metabolites) and sulphasalazine as well as infliximab with a therapeutic drug level. On day 3 of hydrocortisone therapy, he met day Oxford criteria with >8 bloody stools per day and was given faecal microbiota transplantation and subsequently commenced on dietary therapy combining several strategies—(1) increased intake of fermentable fibres, (2) reduced intake of overall and sulfur-containing protein a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…While the pilot nature of this project means that significant associations could not be identified, there was a trend towards participants who met the fibre target having lower symptom severity scores for abdominal pain and incomplete bowel motions, but higher symptom severity scores for flatulence. This trend is in line with our hypothesis that a high fibre diet may assist with the maintenance of new microbiota introduced by FMT human studies [ 13 , 14 , 15 , 32 ] and subsequently sustaining increases in beneficial short chain fatty acids [ 33 ]. Previous work in individuals with IBS suggests that low dose prebiotic supplementation of < 6 g may be associated with improved symptoms, while higher doses or inulin-type fructan supplements may increase gastrointestinal symptoms, such as bloating and flatulence [ 34 ].…”
Section: Discussionsupporting
confidence: 88%
“…While the pilot nature of this project means that significant associations could not be identified, there was a trend towards participants who met the fibre target having lower symptom severity scores for abdominal pain and incomplete bowel motions, but higher symptom severity scores for flatulence. This trend is in line with our hypothesis that a high fibre diet may assist with the maintenance of new microbiota introduced by FMT human studies [ 13 , 14 , 15 , 32 ] and subsequently sustaining increases in beneficial short chain fatty acids [ 33 ]. Previous work in individuals with IBS suggests that low dose prebiotic supplementation of < 6 g may be associated with improved symptoms, while higher doses or inulin-type fructan supplements may increase gastrointestinal symptoms, such as bloating and flatulence [ 34 ].…”
Section: Discussionsupporting
confidence: 88%
“…Beyond a single pilot study, longevity of efficacy of FMT following an induction regimen is limited. Sood et al reported significantly higher rates of endoscopic and histological remission using 8‐weekly FMT via colonoscopy following a rigorous multi‐session FMT induction, with no difference in steroid‐free remission between FMT and placebo groups at 48 weeks 6,9 . Only one other FMT study in UC has provided functional metagenomic data, similarly showing an increase in alpha‐diversity following FMT in those who achieved remission, as well as enrichment in SCFA‐producing organisms including E .…”
Section: Discussionmentioning
confidence: 99%
“…Single‐donor FMT was prepared and administered as per a previously described protocol 6 . Following a polyethylene glycol bowel preparation, 200 mL of thawed fecal suspension was instilled into the patient's caecum via colonoscopy.…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…There are reports that the use of FMT in patients with UC resulted in long-term clinical remission, which necessitates further research in this field. Costello et al [79] presented a case of a 19-year-old man treated in the past with mesalazine, azathioprine and infliximab, currently with a severe UC relapse, who received FMT with a very good effect-the patient was in clinical and endoscopic remission 8 weeks after FMT. Additionally, after 12 months of follow-up, the patient was in clinical and endoscopic remission of UC.…”
Section: Fecal Microbiota Transplantation In Inflammatory Bowel Diseasesmentioning
confidence: 99%